2018
DOI: 10.1002/clc.22899
|View full text |Cite
|
Sign up to set email alerts
|

Early effects of empagliflozin on exercise tolerance in patients with heart failure: A pilot study

Abstract: In this pilot study, empagliflozin was associated with 1-month improvement in exercise capacity in T2DM patients with symptomatic HF. This beneficial effect was also found for other surrogates of severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 12 publications
1
25
0
Order By: Relevance
“…Limited data are available on functional improvement of metabolic treatments in HF ( Table 2). 54–60 In a small study, a beneficial effect of metformin on peak VO 2 was not confirmed ( P = 0.08). However, a significant improvement of the slope of the ratio of minute ventilation to carbon dioxide production was present (from 32.9 ± 15.9 to 28.1 ± 8.8, P = 0.034), which reflects cellular metabolism independent of oxygen uptake and has a strong prognostic power in HF 55 .…”
Section: Co‐morbidities Of Heart Failurementioning
confidence: 94%
“…Limited data are available on functional improvement of metabolic treatments in HF ( Table 2). 54–60 In a small study, a beneficial effect of metformin on peak VO 2 was not confirmed ( P = 0.08). However, a significant improvement of the slope of the ratio of minute ventilation to carbon dioxide production was present (from 32.9 ± 15.9 to 28.1 ± 8.8, P = 0.034), which reflects cellular metabolism independent of oxygen uptake and has a strong prognostic power in HF 55 .…”
Section: Co‐morbidities Of Heart Failurementioning
confidence: 94%
“…However, those not on loop diuretics did not experience the same benefit. It is hypothesized that the synergistic effect of the two medications is due to increased sodium delivery to the distal tubules, which amplifies the natriuretic effect of diuretics 56,57…”
Section: Use In the Treatment Of Type 2 Diabetesmentioning
confidence: 99%
“…To date, two pilot studies have investigated whether empagliflozin improves cardiorespiratory fitness in patients with T2D with heart failure. Núñez et al[45] showed that short-term (4 wk) empagliflozin treatment increased VO 2peak by 1.21 mL/kg per minute (11.1%) from baseline. Conversely, Carbone et al[46] showed that empagliflozin treatment for 4 wk did not significantly improve VO 2peak (14.5 mL/kg vs 15.8 mL/kg per minute).…”
Section: Sglt2 Inhibitors and Cardiorespiratory Fitnessmentioning
confidence: 99%
“…Intriguingly, patients concomitantly treated with loop diuretics demonstrated improved VO 2peak (+0.9 mL/kg per minute), whereas those without loop diuretics demonstrated a decrease in VO 2peak (−0.9 mL/kg per minute). Indeed, all patients in the study by Núñez et al[45] received loop diuretics. The authors hypothesized that empagliflozin acts on the proximal renal tubules by interacting with sodium/hydrogen exchangers, thereby increasing sodium delivery at the distal renal tubules and enhancing the effect of loop diuretics[47,48].…”
Section: Sglt2 Inhibitors and Cardiorespiratory Fitnessmentioning
confidence: 99%